CAPACITY FOR WORK AND CARDIOVASCULAR RISK AMONG PREFECTURAL WORKERS ON A UNIVERSITY CAMPUS - Aline Loiola Moura; Maria do Carmo Lourenço Haddad; José Carlos Dalmas; Vanda Elisa Andres Felli; Paloma de Souza Cavalcante Pissinati (Universidade Federal do Paraná, 2015)
This study aimed to ascertain the relationship of the Work Ability Index with Cardiovascular Risk in workers of the prefecture on a university campus. It is descriptive, exploratory, transversal and quantitative research undertaken in 2012 through the analysis of medical records of 226 workers who underwent regular examinations. Cardiovascular risk was calculated using the Framingham Risk Score. It was observed that 85.0% of the workers were aged over 40 years old. Regarding work capacity, 42.5% presented inadequate capacity. It was identified that 31.2% of the workers had a risk score between medium (20.8%) and high (10.4%) for developing cardiovascular diseases within 10 years. It is concluded that in spite of there being no significant association (p<0.05) between the workers with inadequate capacity for work and those who presented medium and high cardiovascular risk, there was a high number of workers with cardiovascular risk factors.